2005
DOI: 10.1128/aem.71.10.5665-5677.2005
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the Marine Roseobacter Lineage

Abstract: 3Despite the overwhelming bacterial diversity present in the world's oceans, the majority of recognized marine bacteria fall into as few as nine major clades (36), many of which have yet to be cultivated in the laboratory. Molecular-based approaches targeting 16S rRNA genes demonstrate that the Roseobacter clade is one of these major marine groups, typically comprising upwards of 20% of coastal and 15% of mixed-layer ocean bacterioplankton communities (see, e.g., references 36, 37, 42, 98, and 109). Roseobact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
756
5
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 771 publications
(783 citation statements)
references
References 123 publications
21
756
5
1
Order By: Relevance
“…Finally, besides differences related to cell viability, no other differences in measured grazing rates were seen when using the two bacterial strains, even though they belong to distant phylogenetic groups with different life strategies. Members of the Roseobacter lineage tend to be free-living bacteria and typical of somewhat rich conditions (Buchan et al, 2005), whereas flavobacteria tend to be particle-associated bacteria with high exoenzymatic activity (Kirchman, 2002). In our study, Roseobacter and flavobacteria cells were ingested equally by MAST-4, so these important differences in phylogeny and life strategy did not determine prey preference.…”
Section: Grazing Rates Of Uncultured Flagellatesmentioning
confidence: 65%
See 1 more Smart Citation
“…Finally, besides differences related to cell viability, no other differences in measured grazing rates were seen when using the two bacterial strains, even though they belong to distant phylogenetic groups with different life strategies. Members of the Roseobacter lineage tend to be free-living bacteria and typical of somewhat rich conditions (Buchan et al, 2005), whereas flavobacteria tend to be particle-associated bacteria with high exoenzymatic activity (Kirchman, 2002). In our study, Roseobacter and flavobacteria cells were ingested equally by MAST-4, so these important differences in phylogeny and life strategy did not determine prey preference.…”
Section: Grazing Rates Of Uncultured Flagellatesmentioning
confidence: 65%
“…In addition to the in situ sample we analyzed a sample from an unamended incubation (Massana et al, 2006b), which promote the growth of uncultured HF and therefore increase the chances of finding specific predators. For the second objective, besides the standard FLB, we used live bacteria that affiliate to the well-represented marine groups Roseobacter and Flavobacteriaceae (Kirchman, 2002; Buchan et al, 2005;Alonso-Sáez et al, 2007). The strains we used as tracers were isolated from the sampling point (Blanes Bay) and were too scarce in the original sample to interfere with the grazing experiments.…”
Section: Experimental Settingsmentioning
confidence: 99%
“…The possibility of widespread conservation of GTA production in this particular group of bacteria is especially interesting because roseobacters (within the order Rhodobacterales) appear to account for >25% of the total bacterial and archaeal community in some marine environments 47 . Therefore, GTAs could make up a sizable portion of the viral community in places where the abundance of Rhodobacterales members is high.…”
Section: Cihr Author Manuscript Cihr Author Manuscriptmentioning
confidence: 99%
“…However, several studies have indicated that fosmid clone DNA libraries are not fully consistent with other assessments of natural microbial communities, with a poor representation of key members such as SAR11 (Suzuki et al, 2004;DeLong et al, 2006;Gilbert et al, 2008) and a high dominance of Roseobacter spp. (Suzuki et al, 1997;Buchan et al, 2005). In contrast to an estimated 25% abundance of SAR11 in marine microbial communities from plasmid libraries (Giovannoni et al, 2005) and 12-37% abundance from direct counting of SAR11 using fluorescent in situ hybridization (Mary et al, 2006), Gilbert et al (2008) isolated only a single clone containing a 16S rRNA gene with homology to the SAR11 clade from a marine surface water fosmid library of 10 000 clones.…”
Section: Introductionmentioning
confidence: 99%